Modeling drift and fate of microplastics in the Baltic Sea - Murawski, Jens; She, Jun; Frishfelds, Vilnis (Frontiers in Marine Science, 2022)
Marine plastic litter has been recognized as a growing problem and a threat to the marine environment and ecosystems, although its impacts on the marine life are still largely unknown. Marine protection and conservation actions require detailed knowledge of the marine pathways, sources and sinks of land emitted plastic pollution. Model based assessments provide a systematic way to map the occurrence of micro plastics in the marine environment, and to link the coastal sources to the accumulation zones in the sea. New modelling capacities have been developed, that include relevant key processes, i.e., currents and wave induced horizontal and vertical transport, biofilm growth on the particle surface, sinking and sedimentation. Core engine is the HIROMB-BOOS (HBM) ocean circulation model, which has been set-up for the Baltic Sea in high, eddy permitting resolution of 900m. We introduce the 3D modelling tool for microplastics and demonstrate its ability to reproduce drift pattern of microplastics in the Baltic Sea. The results of a multi-year run 2014-2019 provide the basis for an extensive validation study, which allows the evaluation of the model quality. The assessments focus on three types of microplastics, from car tyres and household products, with different density and particle size, which cover a broad range of land emitted microplastic pollution. We show that the model is applicable to the task of identifying accumulations zones in the Baltic Sea, and that it can be a useful tool to support the study of environmental impacts of microplastics in the Baltic Sea. Our results suggest that microplastic concentrations in coastal regions close to major sources reach values above 0.0001 g/m3 near the surface in areas with a Baltic Sea coverage of 6.8%-20.7% for household microplastics and 37.8% for tyre wear microplastics, dependent on buoyancy of the plastic material and the amount of discharge.